A causal relationship between irritability and cardiovascular diseases: a Mendelian randomization study - Cai, Dihui; Fu, Yin; Song, Yongfei; Lin, Hui; Ba, Yanna; Lian, Jiangfang (Frontiers in Cardiovascular Medicine, 2023)
Background Observational studies have suggested that irritability is associated with a higher risk of cardiovascular disease (CVD). However, the potential causal association is not clear. Therefore, we used Mendelian randomization (MR) analysis to assess the causal association of irritability with CVD risk. Methods A two-sample MR analysis was performed to confirm the causal association of irritability with the risk of several common CVDs. The exposure data were derived from the UK biobank involving 90,282 cases and 232,386 controls, and outcome data were collected from the published genome-wide association studies (GWAS) and FinnGen database. Inverse-variance weighted (IVW), MR-Egger, and weighted median methods were performed to assess the causal association. Furthermore, the mediating effect of smoking, insomnia, and depressed affect was explored by using a two-step MR. Results The MR analysis indicated that genetically predicted irritability increased the risk of CVD, including coronary artery disease (CAD) (Odds ratio, OR: 2.989; 95% confidence interval, CI: 1.521–5.874, p = 0.001), myocardial infarction (MI) (OR: 2.329, 95% CI: 1.145–4.737, p = 0.020), coronary angioplasty (OR: 5.989, 95% CI: 1.696–21.153, p = 0.005), atrial fibrillation (AF) (OR: 4.646, 95% CI: 1.268–17.026, p = 0.02), hypertensive heart disease (HHD) (OR: 8.203; 95% CI: 1.614–41.698, p = 0.011), non-ischemic cardiomyopathy (NIC) (OR: 5.186; 95% CI: 1.994–13.487, p = 0.001), heart failure (HF) (OR: 2.253; 95% CI: 1.327–3.828, p = 0.003), stroke (OR: 2.334; 95% CI: 1.270–4.292, p = 0.006), ischemic stroke (IS) (OR: 2.249; 95% CI: 1.156–4.374, p = 0.017), and ischemic stroke of large-artery atherosclerosis ISla (OR: 14.326; 95% CI: 2.750–74.540, p = 0.002). The analysis also indicated that smoking, insomnia, and depressed affect play an important role in the process of irritability leading to cardiovascular disease. Conclusion Our findings support the first genetic evidence of the causality of genetically predicted irritability with the risk of developing into CVDs. Our results deliver a viewpoint that more early active interventions to manage an individual's anger and related unhealthy lifestyle habits are needed to prevent the occurrence of adverse cardiovascular events.